PENERAPAN METODE RCM PADA MESIN SUPER MIXER DALAM INDUSTRI FARMASI SEBAGAI PREVENTIF KERUSAKAN BEARING MOTOR LISTRIK - Effendi, Fadli; Triyanto , Aripin (Komunitas Menulis dan Meneliti (Kolibi), 2024)
This research focuses on analyzing damage to electric motor bearings in super mixer machines in the pharmaceutical industry using the RCM method. Mixer machines are a vital component in the pharmaceutical production process, used to mix ingredients with high precision. Failure of these machines can cause significant production disruptions. The power produced increases with increasing load, indicating the efficiency of the machine in converting electrical energy into mechanical energy. The results showed that after implementing RCM, the machine was free from failure for 109 days, which was 38.4% of the total observation duration (284 days). This shows that RCM is effective in reducing the incidence of damage, although there is room for further improvement. In this research, measurements and analysis were carried out on the voltage, current and power of the super mixer machine at various load conditions, namely 0 kg, 25 kg, 40 kg, 50 kg and 75 kg. Evaluation results show that the voltage, current and power of the machine vary depending on the applied load, with indications that higher loads tend to cause increased current and decreased voltage, which can affect machine performance. Based on the data analysis, it was found that the optimal load for super mixer machine operation is in the range of 25 kg to 50 kg, where the machine shows stable and efficient performance. By implementing the developed maintenance strategy, it is hoped that it can increase the reliability and performance of super mixer machines, reduce the frequency and duration of downtime, and optimize production processes in the pharmaceutical industry. This research makes a significant contribution to the development of effective industrial machine maintenance strategies and can be applied to similar machines in various industries.